Asymmetric Catalytic Assembly of Triple‐Columned and Multilayered Chiral Folding Polymers Showing Aggregation‐Induced Emission (AIE). Issue 7 (28th January 2022) - Wang, Jia‐Yin; Tang, Yao; Wu, Guan‐Zhao; Zhang, Sai; Rouh, Hossein; Jin, Shengzhou; Xu, Ting; Wang, Yu; Unruh, Daniel; Surowiec, Kazimierz; Ma, Yanzhang; Li, Yunze; et al.
Abstract: Invited for the cover of this issue are Guigen Li's groups at Texas Tech University and Nanjing University. The cover artwork shows that chirality patterns exist from universal to molecular levels showing light emission properties. Read the full story of multilayer 3D chirality and its asymmetric catalytic synthesis at 10.1002/chem.202104102 . Abstract : " The resulting multiple π ‐assemblies exhibited remarkable optical properties in aggregated states… as well as reversible redox properties ." This and more about the story behind the front cover can be found in the article at 10.1002/chem.202104102 ).